Pore fracture structure evolution and damage failure mechanism of hot dry rock induced by temperature impact effect - Yong SUN; Cheng ZHAI; Yuzhou CONG; Yangfeng ZHENG; Wei TANG; Shuai WANG; Yongshuai LAI; Yu WANG; Aikun CHEN (Meitan xuebao)
The geothermal resource originating from the hot dry rock is a form of clean and renewable energy, which has the advantages of stable, efficient, and permanent. The foremost obstacle hindering its development resides in the construction of fracture channels for seepage and heat transfer within deep reservoirs characterized by low porosity and permeability. The conventional hydraulic fracturing method has high initiation pressure, single fracture shape, and difficult expansion under the constraint of deep high stress. Therefore, a liquid nitrogen cyclic cold shock method was proposed in this study. Liquid nitrogen is injected into the high-temperature rock periodically, inducing robust thermal stress through the temperature shock effect, thereby forming a complex fracture network. To study the damage mechanism of hot dry rock influenced by the temperature shock effect, the hot dry rock was subjected to a cyclic liquid nitrogen cooling treatment. The changes in temperature distribution, pore structure, and mechanical characteristics were tested and the cascade failure mechanism of “temperature shock-pore development-mechanical damage” was analyzed. The main conclusions are as follows: liquid nitrogen cold shock causes a temporal-spatial drastic change in the temperature field, marked by a high cooling rate and a large temperature gradient, and the induced thermal stress reaches up to 6.75 MPa. The number of pores increases, the size expands, and the increase in micro and mesopores is most significant, with a maximum porosity of 10.45%. Under the influence of high-temperature differences and multiple cold shocks, the number of macropores and fractures increases, giving rise to the formation of an interconnected network of fractures. This further increases the plasticity of the hot dry rock, reducing the tensile strength to only 1.70 MPa with a smaller damage threshold. Temperature shock induces mineral grain shrinkage, generating tensile stress at the boundaries between grains. When its value exceeds the tensile strength, tensile cracks will be generated. Pores and cracks mainly occur at the boundaries and within the interior of quartz grains. Temperature is the main controlling factor of hot dry rock damage, and the cyclic cold shocks serve to ensure sustained damage. The differences in the thermal expansion coefficients of mineral grains, the rapid cooling of liquid nitrogen, and the fatigue damage of cyclic shock are the main reasons for the damage of hot dry rock.